2010
DOI: 10.1111/j.1751-7176.2010.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Liddle Syndrome Phenotype Among Hypertensive US Veterans in Northwest Louisiana

Abstract: J Clin Hypertens (Greenwich). Liddle syndrome (LS) is an autosomal dominant disorder due to a gain‐of‐function mutation in the epithelial Na+ channel and is perceived to be a rare condition. A cross‐sectional study of 149 hypertensive patients with hypokalemia (<4 mmol/dL) or elevated serum bicarbonate (>25 mmol/dL) was conducted at a Veterans’ Administration Medical Center Hypertension Clinic in Shreveport, LA. Data on demographics, blood pressure, and select blood tests were collected and expressed as percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…However, an extensive study that included a sample of 330 Chinese young hypertensive patients revealed that 1.5% of the patients had mutations associated with a loss of the PY motif (Wang et al, 2015). In a retrospective study in a cohort of 149 hypertensive US veterans, 6% were found to have biochemical abnormalities compatible with Liddle syndrome (Tapolyai et al, 2010). Thus, Liddle syndrome may be a common cause of monogenic hypertension in some populations (Padmanabhan et al, 2015).…”
Section: Diseases Associated With Enac Mutationsmentioning
confidence: 99%
“…However, an extensive study that included a sample of 330 Chinese young hypertensive patients revealed that 1.5% of the patients had mutations associated with a loss of the PY motif (Wang et al, 2015). In a retrospective study in a cohort of 149 hypertensive US veterans, 6% were found to have biochemical abnormalities compatible with Liddle syndrome (Tapolyai et al, 2010). Thus, Liddle syndrome may be a common cause of monogenic hypertension in some populations (Padmanabhan et al, 2015).…”
Section: Diseases Associated With Enac Mutationsmentioning
confidence: 99%
“…Variants of Liddle’s syndrome, a renal tubular sodium channel mutation that causes salt and water retention, accounted for 5% of hypertension in black people in the UK [43], 6% of hypertension in black people in South Africa (and 20% of the Khoi San people of the Kalahari) [44], and 6% of patients attending a Veterans Administration clinic in Louisiana [45]. The specific therapy for Liddle’s variants is amiloride.…”
Section: Blood Pressure Controlmentioning
confidence: 99%
“…Up until 2008, only 30 patients affected with this monogenetic disorder had been reported in the world [9]. Two small single-center studies have estimated the prevalence to be about 1.52% and 6% among hypertensive patients with genetic testing and phenotypical LS, respectively [3-4]. Our knowledge about LS is evolving, given its relative rarity.…”
Section: Introductionmentioning
confidence: 99%